Hubungan antara Pemberian ASI Eksklusif dan Perkembangan Anak di RSUD Wangaya Denpasar, Bali, Indonesia - Fransiskus Aditya Kristianto; I Wayan Bikin Suryawan; I Kadek Suarca (PT Kalbe Farma Tbk., 2023)
Background: Exclusive breastfeeding is considered as one of many crucial factors in child development. The research was conducted with the aim of to determine the relationship between exclusive breastfeeding and child development. Method: An observational analytic study with cross-sectional design; the independent variable was exclusive breastfeeding and the dependent variable was child development according to KPSP score. A total of 86 samples were obtained using consecutive sampling method. Data were analyzed using the Chi-square test. Result: A significant positive correlation between exclussive breastfeeding and child development (p=0.035). Conclusion: There is a correlation between exclussive breastfeeding and child development in children at Wangaya Denpasar Regional Hospital.